Dynamical diffeomorphisms - Ferrero, Renata; Percacci, Roberto (Classical and Quantum Gravity, 2021)
We construct a general effective dynamics for diffeomorphisms of spacetime, in a fixed external metric. Though related to familiar models of scalar fields as coordinates, our models have subtly different properties, both at kinematical and dynamical level. The energy–momentum (EM) tensor consists of two independently conserved parts. The background solution is the identity diffeomorphism and the EM tensor of this solution gives rise to an effective cosmological constant.<br